Yiallouras, Christos - (:unkn) unknown (My University, 2026)
Christos Yiallouras (born on 06.04.1983), has a degree in Computer Science from the Frederick University Cyprus, 2015 obtain doctoral degree in biomedical engineering at the City University of London, UK. His research interests include the development of software for controlling MRI compatible high intensity focus ultrasound (HIFU) systems, as well as for the design of MRI compatible robotic devices. He works in software development department of MEDSONIC LTD (4 years), and as a research associate in the Department of Electrical Engineering of the Cyprus University of Technology.